Finding a place for art archives; Reflections on archiving Indonesian and Southeast Asian art - Wardani, Farah (Wacana, Journal of the Humanities of Indonesia, 2019)
This article is a collection of reflections of art archiving work in Indonesia and Southeast Asia, focusing on building an Indonesian art archive at Indonesian Visual Art Archive (IVAA), 2006-2015, and Southeast Asian art archives at National Gallery Singapore, from 2015 to the present. The article provides insights, learning points, and perspectives on the importance of art archives to support art historical research and the development of art history in Southeast Asia. It sheds light on the challenges, opportunities, and current developments in the field of building archives.